TÜRKÜLERDE TÜRK’ÜN COĞRAFYASI - MAHMUT DELEN (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2024)
In the search, the names of countries and cities outside Turkey mentioned in folk songs, were analyzed using document analysis technique. Folk song texts in the context of place names were divided into themes. The classified data were analyzed in the light of the information given by the place names; which geographies were the subject of the folk songs, how these geographies were depicted and the mentioning frequencies of the geographies in the folk songs were revealed. Based on the data obtained, it has been observed that even if Turks do not have political sovereignty in the geographies they have made homeland, they make these places the subject of their folk songs due to cultural unity. In addition, in this context, when the cultural traces of folk songs are evaluated by centring on the place references in their texts rather than the regions where the folk songs were collected, it is understood that the geography where the cultural traces of the folk songs extend goes far beyond the basin of folk song collection.